Farmers Decision Making Pattern on Agricultural Innovations: A Process Analysis - Chandre Gowda, M. J; Dolli, Shrishail S; Dixit, Sreenath; Durga Prasad, M. V.; Saravanan, D. (Indian Journal of Extension Education, 2022)
Decision making on new practices in crop production and marketing among farmers was studied in different agro-climatic situations of Gujarat and Karnataka. The process was analyzed using the initiation pattern, activities engaged in and sources consulted before decision-making based on primary data collected from 787 farmers cultivating paddy, cotton, groundnut, maize and potato. Five patterns of initiation to decision making were identified, which varied for different functional areas and crops. Activities that followed indicated that majority of farmers resorted to quick decision making, mostly based on a single source of information. Based on the pattern of initiation, sources of information and activities, decision making was broadly categorized as imitation, induced and informed. Informed decision-making was more prevalent in the case of groundnut and maize crops, which were less problematic crops. On the contrary, cotton and potato farmers resorted to induced decision-making, probably due to complexity of problems in pests, micronutrient and marketing. In paddy, a traditional food crop cultivated in a more homogenous environment, farmers resorted to imitative decision making. Maximizing informed decisions while facilitating purposeful imitation could be a desirable strategy, although the specific strategies could be location and context-specific.